Prevalence and predictors of hand hygiene compliance in clinical, surgical and intensive care unit wards: results of a second cross- sectional study at the Umberto I teaching hospital of Rome - Ceparano, Mariateresa; Covelli, Antonio; Baccolini, Valentina; Isonne, Claudia; Sciurti, Antonio; Migliara, Giuseppe; De Giusti, Maria; Marzuillo, Carolina; Villari, Paolo (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Introduction. Hand hygiene is the most cost-effective procedure for the prevention of healthcare-associated infections, but healthcare worker compliance is often insufficient. Research design. The objective of this second cross-sectional study was to quantify hand hygiene compliance among the healthcare workers of a large teaching hospital, to explore associated factors and to compare results to those of the 2021 study. Methods. In 2022, educational sessions were conducted within each hospital department during which hospital healthcare workers received tailored feedback on the hand hygiene compliance registered in the previous year. Then, one month later, direct observations of hand hygiene compliance with five World Health Organization recommendations were collected again by anonymous observers in each ward. Data were grouped by healthcare area (clinical, surgical and intensive care), and three multivariable logistic regression models were built to identify predictors of hand hygiene compliance. Results. Overall, 5,426 observations were collected by 73 observers in three weeks. Hand hygiene compliance was 79.7%, 73.5% and 63.1% in clinical, surgical and intensive care areas, respectively, increasing in clinical wards but decreasing in surgical departments compared to the 2021 study. The multivariable analyses showed that hand hygiene compliance after patient contact was consistently higher than before patient contact, while there was some variability in compliance with other factors across the three areas.Conclusion. The study found suboptimal adherence to good hand hygiene practice, with the lowest rates observed before patient interaction, which, together with the variability recorded across departments, underscores the challenges involved in achieving a uniform level of compliance. Hence, additional training is essential to raise awareness among healthcare workers, while repeating this survey over time will also be crucial, so that hand hygiene compliance can be monitored and any major issue identified.